Síndrome de Burnout y su relaicón en la atención que brindan a los pacientes los médicos tratantes del hospital provincial general Isidro Ayora Loja periodo septiembre 2013 - enero 2014 - Patiño Ochoa, Andrea Elizabeth (2013)
Burnout is defined as a response to chronic job stress composed of attitudes and negative feelings toward people with which to work and to the professional role itself, as well as the experience of being emotionally drained, the main causes of burnout in psychologically deal with excess stress and work, which leads to serious physical and psychological and even the rise to numerous sick leave consequences. The present research is descriptive - cross type , formulated the following objectives : To determine the relationship between burnout syndrome and care provided to patients attending physicians of Isidro Ayora Hospital ; identify the presence of burnout syndrome in selected medical and establish the quality of care provided to patients. Once applied the MBI test in 40 attending physicians of Hospital Isidro Ayora Loja, we can say that 40 % have burnout syndrome , while 30 % reported emotional exhaustion , 25% depersonalization and 5% reduced personal accomplishment ; while in 120 patients surveyed the quality of care received during the consultation 48% considered as fair , 35 % reported as good and 17% as poor . Thus concluding that the presence of the Burnout syndrome in the treating physicians if it interferes with the quality of care received by patients in the Isidro Ayora Hospital Loja. KEYWORDS: Burnout syndrome, Quality of Care.